Mesoporous amorphous binary Ru–Ti oxides as bifunctional catalysts for non-aqueous Li–O2 batteries. (8th March 2017) - Kim, Jisu; Jo, HeeGoo; Wu, Mihye; Yoon, Dae-Ho; Kang, Yongku; Jung, Ha-Kyun
Abstract: Mesoporous amorphous binary Ru–Ti oxides were prepared as bifunctional catalysts for non-aqueous Li–O2 batteries, and their electrochemical performance was investigated for the first time. A Li–O2 battery with mesoporous amorphous binary Ru–Ti oxides exhibited a remarkably high capacity of 27100 mAh g −1 as well as a reduced overpotential. A GITT analysis suggested that the introduction of amorphous TiO2 to amorphous RuO2 was responsible for the enhanced kinetics toward both the oxygen reduction reaction and oxygen evolution reaction. Excellent cyclic stability up to 230 cycles was achieved, confirming the applicability of the new bifunctional catalyst in non-aqueous Li–O2 batteries.